Breviscapine alleviates NASH by inhibiting TGF‐β‐activated kinase 1‐dependent signaling. Issue 1 (19th December 2021) - Lan, Tian; Jiang, Shuo; Zhang, Jing; Weng, Qiqing; Yu, Yang; Li, Haonan; Tian, Song; Ding, Xin; Hu, Sha; Yang, Yiqi; Wang, Weixuan; Wang, Lexun; et al.
Abstract: Background and Aims: NAFLD is a key component of metabolic syndrome, ranging from nonalcoholic fatty liver to NASH, and is now becoming the leading cause of cirrhosis and HCC worldwide. However, due to the complex and unclear pathophysiological mechanism, there are no specific approved agents for treating NASH. Breviscapine, a natural flavonoid prescription drug isolated from the traditional Chinese herb Erigeron breviscapus, exhibits a wide range of pharmacological properties, including effects on metabolism. However, the anti‐NASH efficacy and mechanisms of breviscapine have not yet been characterized. Approach and Results: We evaluated the effects of breviscapine on the development of hepatic steatosis, inflammation, and fibrosis in vivo and in vitro under metabolic stress. Breviscapine treatment significantly reduced lipid accumulation, inflammatory cell infiltration, liver injury, and fibrosis in mice fed a high‐fat diet, a high‐fat/high‐cholesterol diet, or a methionine‐ and choline‐deficient diet. In addition, breviscapine attenuated lipid accumulation, inflammation, and lipotoxicity in hepatocytes undergoing metabolic stress. RNA‐sequencing and multiomics analyses further indicated that the key mechanism linking the anti‐NASH effects of breviscapine was inhibition of TGF‐β‐activated kinase 1 (TAK1) phosphorylation and the subsequent mitogen‐activated protein kinase signaling cascade. Treatment with the TAK1 inhibitor 5Z‐7‐oxozeaenol abrogated breviscapine‐mediated hepatoprotection under metabolic stress. Molecular docking illustrated that breviscapine directly bound to TAK1. Conclusion: Breviscapine prevents metabolic stress–induced NASH progression through direct inhibition of TAK1 signaling. Breviscapine might be a therapeutic candidate for the treatment of NASH.